Shamrocks and Oil Slicks : a People's Uprising Against Shell Oil in County Mayo, Ireland. - Wilcox, Fred A. (Monthly Review Press, 2019)
"Shamrocks & Oil Slicks "tells the story of County Mayo-the fishermen, farmers, teachers, business people-who, motivated by love for their environment, their community, and their country, fought Shell Oil, one of the planet's most powerful destroyers to a standstill. The people launched a nonviolent resistance movement that was to last some fifteen years. Residents from all walks of life were beaten by police, threatened by mercenaries, sent to jail and prison. Abandoned by the state and their church, insulted and maligned by the media, they refused to give up fighting to save their environment and their heritage"--